Relationship between Lords and Gentry in England in Second Half of 15th Century in Context of ‘Bastard Feudalism’ Concept: a Prosopographic Analysis - A. G. Prazdnikov (Научный диалог, 2022)
“Bastard feudalism” is a system of patronage-client relations that existed in England in the late Middle Ages, opposed to the vassal-seigneurial relations of classical feudalism. This concept has been used in historiography since the 19th century, but is still debatable. The relevance of the study is due to the question of the degree of “bastard feudalism” relations distribution in society. Based on the sources, a prosopographic database of active participants in the Wars of the Roses (1455–1487) was formed, a significant part of which were secular lords and representatives of the middle and lower nobility (gentry): knights, squires and gentlemen. The retinues of the lords had a motley social composition, but, as a rule, included precisely the nobles. Analysis of the database showed that at least 16 % of the representatives of the gentry were in the service or were part of the entourage of the lords who supported the Lancasters or Yorks. Most of the gentry did not belong to the retinue of the lords, but were dependent on them and were recruited into military service in cases of aggravation of the socio-political conflict.